2002
DOI: 10.1200/jco.2002.02.108
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Double-Blind, Placebo-Controlled Trial of Marimastat After Response to First-Line Chemotherapy in Patients With Small-Cell Lung Cancer: A Trial of the National Cancer Institute of Canada-Clinical Trials Group and the European Organization for Research and Treatment of Cancer

Abstract: Treatment with marimastat after induction therapy for SCLC did not result in improved survival and had a negative impact on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(84 citation statements)
references
References 21 publications
0
81
0
3
Order By: Relevance
“…This assumption is supported by the disappointing outcome of several recent clinical studies using such agents (Bramhall et al, 2001;Coussens et al, 2002;Shepherd et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…This assumption is supported by the disappointing outcome of several recent clinical studies using such agents (Bramhall et al, 2001;Coussens et al, 2002;Shepherd et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…This dose was chosen based on pharmacokinetic data from a phase 1 trial of marimastat in patients with advanced cancer, which suggested that this dose would generate plasma concentrations in the range required to inhibit the target enzymes, MMP2 and MMP9, while minimising the incidence of musculoskeletal side effects (Wojtowicz-Praga et al, 1998). This dose level has been used in several phase II and III trials of marimastat as a single agent (Bramhall et al, 2002;Miller et al, 2002;Shepherd et al, 2002). Fragmin was administered by a once daily subcutaneous injection at a dose of 200 units kg À1 for 4 weeks, after which the dose was reduced to 5000 units per day for the duration of the study.…”
Section: Methodsmentioning
confidence: 99%
“…One is that the molecular target was not essential for growth, invasion, or metastasis of the tumor, and this hypothesis may explain the negative results for matrix metalloprotease inhibitors 15) and small molecules against vascular endothelial growth factor (VEGF) tyrosine kinase.…”
Section: Reasons For Negative Phase III Trialsmentioning
confidence: 99%